A Marketplace System Web-Based Using The Extreme Programming Method - Hadaya, M. Syahan Afdhal; Utomo, Pradita Eko Prasetyo; Bintana, Rizqa Raaiqa (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2025)
This study aims to design and develop a web-based marketplace information system for X University using the Extreme Programming methodology while also evaluating the functionality of its features. The selected method, Extreme Programming (XP), focuses on rapid iterative development and effective communication with stakeholders. The system was successfully designed and developed through three iterative cycles. During the first iteration, development was conducted by implementing the pre-planned design based on the established release plan. The second iteration continued with the same development process, adhering to the outlined steps in the release plan. In the third iteration, additional actors and new features were incorporated into the system. To assess the system"™s performance, functionality testing was conducted using the Black Box Testing method. The results indicated that the system operated optimally, achieving a 100% success rate. This research also identified challenges faced by students and users when conducting literature reviews and purchasing products. One key issue is the difficulty users experience in accessing real-time product stock information. Additionally, buyers are still required to visit X University in person to make purchases. To address these challenges, the development of an online marketplace is necessary to facilitate seamless transactions. Thus, this research was carried out with the goal of providing a practical solution to these existing problems.